Isolation and Identification of Ice-Nucleating-Active Bacteria from Indonesian Edible Leafy Plant Poh-Pohan (Pilea glaberina) - DIANA ELIZABETH WATURANGI; VICKY MEICY; ANTONIUS SUWANTO (Indonesian Society for microbiology, 2008)
Two ice-nucleating-active (INA) bacteria (isolates C and 6) were isolated from poh-pohan (Pilea glaberina), an Indonesian edible leafy plant (lalaban). The maximum nucleation temperature of aqueous suspensions of the two isolates is -5 °C. They were classified as a type II ice nucleator. Microscopic and morphological determination showed that these isolates had yellow pigmentation, rod shape, and were Gram negative. Biochemical analysis indicated that the isolates were exhibited catalase activity, but negative in oxidase and indole assays. DNA sequencing of 16SrRNA gene of isolate A3 showed a 94% similarity to Pseudomonas sp. while isolate A4 showed a 97% similarity to Xanthomonas campestris. To our knowledge, this is the first report of INA bacteria isolated from a tropical edible leafy plant.